2020
DOI: 10.5414/cncs109972
|View full text |Cite
|
Sign up to set email alerts
|

A case report of three children with secondary hypertension caused by Liddle syndrome

Abstract: Background: Liddle syndrome is a monogenetic cause of early-onset hypertension that is associated with hypokalemia and metabolic alkalosis that is inherited in an autosomal dominant fashion with variable penetrance. Case presentation: We present a case report of three children seen at a tertiary children's hospital with varying severity of hypertension and electrolyte disturbances, who had genetic testing performed due to strong family history of hypertension. They were each subsequently found with the same ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…Teoh et al reported three cases of Liddle from Department of Pediatrics, University of Louisville, Kentucky USA with almost similar age group and clinical pictures as our case 8. Patel and Kuriacose reported a case of Liddle syndrome from Johnson City, Tennessee USA, but the age of the patient was 48 years 2.…”
supporting
confidence: 65%
See 3 more Smart Citations
“…Teoh et al reported three cases of Liddle from Department of Pediatrics, University of Louisville, Kentucky USA with almost similar age group and clinical pictures as our case 8. Patel and Kuriacose reported a case of Liddle syndrome from Johnson City, Tennessee USA, but the age of the patient was 48 years 2.…”
supporting
confidence: 65%
“…However, children presenting with hypertension along with electrolyte imbalance should raise suspicion of monogenic causes of hypertension, which include Liddle syndrome, Gordon syndrome and familial hyperaldosteronism. 8 These disorders are called monogenic because they are caused by single gene mutations, which are inherited in Mandelian pattern. 8,9 To investigate further, serum renin and aldosterone should be checked.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of hypertension involves dietary sodium limitations and ENaC blockers such as amiloride and triamterene [28,46].…”
Section: Discussionmentioning
confidence: 99%